2020
DOI: 10.3390/pr8040429
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic Studies on Non-Premixed Oxy-Methane Flames and Separated Oxy-Methane Cold Jets

Abstract: Both cold and flame jets find numerous applications in different fields, ranging from domestic applications to aerospace and space technology. Indeed, the applications of isothermal and non-isothermal jets in the flame heating industry fascinated the researchers to gain an in-depth understanding. Nevertheless, these benefits are not standalone, rather, they are associated with major disadvantages such as improper jet mixing and flame instabilities that require careful remedies. In the present investigation, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…The concluding point revealed that RANS model being an inexpensive and conventional method predicts supersonic core length and decay rate with sufficient accuracy [18]. Furthermore, in a recent study conducted by Jana et al (2020) for subsonic jets using RANS model, it has been observed that shear layer growth is a prominent and rudimentary phenomenon for mass entrainment [19].…”
Section: Introductionmentioning
confidence: 99%
“…The concluding point revealed that RANS model being an inexpensive and conventional method predicts supersonic core length and decay rate with sufficient accuracy [18]. Furthermore, in a recent study conducted by Jana et al (2020) for subsonic jets using RANS model, it has been observed that shear layer growth is a prominent and rudimentary phenomenon for mass entrainment [19].…”
Section: Introductionmentioning
confidence: 99%
“…Another article by Kaushik et al looks into the mixing characteristics of cold and flame jets. Jet mixing has many applications, from household appliances to rocket science [7]. Mixing fuel and an oxidizer in the combustion chamber should occur efficiently and within a small distance to begin efficient burning.…”
mentioning
confidence: 99%